2005
DOI: 10.1096/fj.04-3515com
|View full text |Cite
|
Sign up to set email alerts
|

Brain mitochondria contain aquaporin water channels: evidence for the expression of a short AQP9 isoform in the inner mitochondrial membrane

Abstract: Aquaporins are a family of water channels found in animals, plants, and microorganisms. A subfamily of aquaporins, the aquaglyceroporins, are permeable for water as well as certain solutes such as glycerol, lactate, and urea. Here we show that the brain contains two isoforms of AQP9--an aquaglyceroporin with a particularly broad substrate specificity--and that the more prevalent of these isoforms is expressed in brain mitochondria. The mitochondrial AQP9 isoform is detected as an approximately 25 kDa band in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
99
1

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 48 publications
3
99
1
Order By: Relevance
“…In rats, they further reported a prominent expression of AQP9 in catecholaminergic cell bodies and proximal fibers in the brain stem and hypothalamus but not the habenula or in other monoaminergic cell groups (17). Amiry-Moghaddam et al (16) further demonstrated that AQP9 was present in rat plasma membranes and inner mitochondrial membranes of dopaminergic neurons and astrocytes in the SN, VTA and arcuate nucleus, using immunogold electron microscopy.…”
Section: Distribution Of Aqp9 In the Brainmentioning
confidence: 96%
See 4 more Smart Citations
“…In rats, they further reported a prominent expression of AQP9 in catecholaminergic cell bodies and proximal fibers in the brain stem and hypothalamus but not the habenula or in other monoaminergic cell groups (17). Amiry-Moghaddam et al (16) further demonstrated that AQP9 was present in rat plasma membranes and inner mitochondrial membranes of dopaminergic neurons and astrocytes in the SN, VTA and arcuate nucleus, using immunogold electron microscopy.…”
Section: Distribution Of Aqp9 In the Brainmentioning
confidence: 96%
“…AQP4 is also expressed in ependymal cells of the ventricles but is primarily associated with astrocytic cell membranes (20). Subpopulations of astrocytes also express AQP9 in plasma membranes as well as in inner mitochondrial membranes (16). Moreover, AQP9 is the only aquaporin expressed in neurons, where it is located in the plasma membrane and the inner mitochondrial membrane (16).…”
Section: Aquaporins In the Brainmentioning
confidence: 99%
See 3 more Smart Citations